Model Komunikasi Konten Kuliner pada Akun Instagram @maumakanchanel - Fernanda, Yasmin Dhea; Zuhriah, Zuhriah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This article examines the persuasive communication model in culinary content produced by the Instagram account @maumakanchanel, which serves as a popular reference for promoting local culinary businesses in Medan City. The urgency of this study lies in the role of social media as a strategic promotional platform for micro, small, and medium enterprises (MSMEs), where visual and narrative communication acts as the primary instrument in influencing public consumption preferences. This study employs a qualitative method with a descriptive approach aimed at illustrating the dynamics of messages and persuasive communication strategies in digital content. Data collection techniques include content observation, in-depth interviews with eleven informants comprising account owners, administrators, and active followers, as well as digital documentation. Data analysis was conducted using the Miles, Huberman, and Saldana model, encompassing data condensation, data display, and conclusion drawing. The results indicate that persuasive message construction is formed through a combination of central and peripheral routes as outlined in the Elaboration Likelihood Model (ELM), emphasizing communicator credibility, appealing food visuals, and emotionally engaging, distinctive language styles. The study concludes that the integration of authentic communicator motivation, visual-verbal strategies, and an in-depth understanding of audience dynamics is crucial for the success of culinary communication on social media.